1986
DOI: 10.1007/bf00377113
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Neodiprion sertifer (Hym., Diprionidae) larvae to variation in needle resin acid concentration in Scots pine

Abstract: We have studied how differences in needle resin acid concentrations between two clones of Scots pine influenced larval survival, larval developmental time, and cocoon weight in Neodiprion sertifer. Larvae were reared under controlled conditions in the laboratory on needles showing a three-fold difference, in resin acid concentration. Larval developmental time was significantly longer for larvae fed needles high in resin acids. No significant differences were found in cocoon weight. Larvae fed needles high in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
4
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 47 publications
3
69
4
1
Order By: Relevance
“…Fitness components of herbivorous insects are often negatively correlated with increasing levels of plant allelochemicals (Harborne 1982(Harborne , 1988Rosenthal and Berenbaum 1991;Speight et al 1999) and with morphological features such as trichomes (Gange 1995;Lambert et al 1995) or the toughness of leaves and stems (Raupp 1985;Stevenson et al 1993;Eigenbrode et al 1995). As with resistance, intraspecific variation in host plant quality is often genetically based (Whitham 1983;Larsson et al 1986;McCrea and Abrahamson 1987;Karban 1992).…”
mentioning
confidence: 99%
“…Fitness components of herbivorous insects are often negatively correlated with increasing levels of plant allelochemicals (Harborne 1982(Harborne , 1988Rosenthal and Berenbaum 1991;Speight et al 1999) and with morphological features such as trichomes (Gange 1995;Lambert et al 1995) or the toughness of leaves and stems (Raupp 1985;Stevenson et al 1993;Eigenbrode et al 1995). As with resistance, intraspecific variation in host plant quality is often genetically based (Whitham 1983;Larsson et al 1986;McCrea and Abrahamson 1987;Karban 1992).…”
mentioning
confidence: 99%
“…Similar adverse effects of feeding on non-preferred current-year needles have been observed in the pine-feeding sawfly Neodiprion sertifer (Niemelä et al, 1984). The poorer performance of larvae on current-year needles is likely to be caused by higher concentrations of defensive compounds such as resin acids in younger needles (Hanover, 1975;Larsson et al, 1986). Several studies on pine-feeding insects have documented decreased host plant resistance or increased suitability after defoliation (Niemelä et al, 1984(Niemelä et al, , 1991Wagner & Evans, 1985;McMillin & Wagner, 1997).…”
Section: Discussionmentioning
confidence: 75%
“…C-based defensive compounds, such as resin acids (Larsson et al 1986), phenolics (Giertych et al 2007) and 3-carene monoterpene (Barre et al 2003) have been found to have negative effects on pine sawfly performance. Bryant et al (1983) suggested that plants growing on nutrientpoor sites have a surplus of C from which they can allocate a part to C-based defense compounds.…”
Section: Soil Fertility Effectsmentioning
confidence: 99%
“…Overall, sawfly outbreaks seem to be more frequent and severe on monoculture, evenaged and plantation stands, compared to forests with several tree species, age classes and layers (Geri 1988, McMillin & Wagner 1993. In Scandinavia, the performance of pine sawflies and the frequency, intensity and spatial extent of damage has been related to temperature (Kollberg et al 2015) and host plant quality, especially needle carbohydrate and terpene concentrations (Larsson et al 1986, Lyytikäinen 1994, Kollberg et al 2015. In addition, site and stand characteristics, such as site type and stand age (Larsson & Tenow 1984, De Somviele et al 2007, Nevalainen et al 2015, and natural enemies (Hanski & Parviainen 1985, Kollberg et al 2014) have been observed to modify sawfly performance and affect the level of tree damage.…”
Section: Introductionmentioning
confidence: 99%